Herbal Tea - Nünnerich, Lukas (Satura, 2026)
This poetic short prose explores the fragile boundary between innocence and violence through the eyes of a narrator who witnesses child abuse in a clinical setting. It examines the transformation of healthy bodies into wounded ones — and the emotional impact this has on victims, witnesses, and society as a whole. Beyond that, it asks how deeply the family we are born into shapes our ability to participate in the world.